A Gondwanan Imprint on the Global Diversity and Domestication of the Wine and Cider Yeast Saccharomyces uvarum - Almeida, Pedro (2014)
In addition to Saccharomyces cerevisiae, the cryotolerant yeast species S. uvarum is also used for wine and cider fermentation but nothing is known about its natural history. Here we use a population genomics approach to investigate its global phylogeography and domestication fingerprints using a collection of isolates obtained from fermented beverages and from natural environments on five continents. South American isolates contain more genetic diversity than that found in the Northern Hemisphere. Moreover, coalescence analyses suggest that a Patagonian sub-population gave rise to the Holarctic population through a recent bottleneck. Holarctic strains display multiple introgressions from other Saccharomyces species, those from S. eubayanus being prevalent in European strains associated with humandriven fermentations. These introgressions are absent in the large majority of wild strains and gene ontology analyses indicate that several gene categories relevant for wine fermentation are overrepresented. Such findings constitute a first indication of domestication in S. uvarum.